Spontaneous penile skin gangrene in AIDS - Mallikarjuna N Reddy; A Thyagi; D Sharma; VSNL; Eashwar K Goud (Indian Journal of Urology, 2000)
AIDS is a systematic infection of retrovirus causing immunodeficiency. Many varied manifestations of the dis-ease have been reported. Systemic vasculitis has been re-ported in as one of the manifestations of the syndrome. This has resulted in areas of skin necrosis in varied parts of ′the body. We report a case of penile skin necrosis which occurred spontaneously in a 25-year-old male patient with no evidence of trauma or infection.